2023
DOI: 10.3389/fvets.2022.1037327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative plasma and urine metabolomics analysis of juvenile and adult canines

Abstract: Background and aimsThe metabolomic profile of a biofluid can be affected by age, and thus provides detailed information about the metabolic alterations in biological processes and reflects the in trinsic rule regulating the growth and developmental processes.MethodsTo systemically investigate the characteristics of multiple metabolic profiles associated with canine growth, we analyzed the metabolomics in the plasma and urine samples from 15 young and 15 adult beagle dogs via UHPLC-Q-TOFMS-based metabolomics. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…This indicates that for heterogeneous patient collectives, the BA with the highest concentration may not necessarily be the best choice for diagnostic BA measurements. This finding is in general agreement with previous studies ( 31 , 41 , 42 ). The interindividual BA variations identified in the present study could be of genetic origin and so might just reflect the different genetics of different dog breeds.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This indicates that for heterogeneous patient collectives, the BA with the highest concentration may not necessarily be the best choice for diagnostic BA measurements. This finding is in general agreement with previous studies ( 31 , 41 , 42 ). The interindividual BA variations identified in the present study could be of genetic origin and so might just reflect the different genetics of different dog breeds.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, a study in rats showed significant increase of T-CA with age ( 43 ). However, a previous study using UHPLC-Q-TOFMS-based metabolomics to examine plasma samples from 15 young and 15 adult beagle dogs showed higher plasma levels for the young beagle dogs, at least for T-CA, G-CA, and T-CDCA ( 41 ). This difference might be explained by the study collective (only beagle dogs vs. diverse dog breeds in the present study) or by differences in the absolute age of the groups of young and adult dogs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations